The ecology of an incipient marine biological invasion: the Charru mussel Mytella charruana d?Orbignyi, 1846 (Bivalvia Mytilidae) in Manila Bay, Luzon, Philippines - Vallejo, Jr., Benjamin; Conejar-Espedido, Jeniffer; Manubag, Leanna (2017)
The study documents the initial colonization ecology of the Western Hemisphere?s non-indigenous mytilid Mytella charruana in the Port of Manila, Manila Bay. As part of a monitoring effort to document fouling communities using PICES collectors, a recruitment pulse of Mytella charruana was detected in Jul 2014. The recruits have persisted and established in the port. Also noted was the possible recruitment competition with other indigenous and non-indigenous bivalve species. Mytella recruits during the onset of the southwest monsoon rainy season. Based on Canonical Correspondence Analysis of recruit abundances with water quality parameters, Mytella, the green mussel Perna viridis, Musculista, and Brachidontes have a lower salinity niche and recruits on Amphibalanus and Hydroides biogenic substrates. Also examined was the possible competition between Mytella and Perna viridis, since these species have been used for mariculture. Perna is traditionally cultured in Manila Bay, while Mytella is proposed as a new species for mariculture in the Philippines. Based on the results and its physiological ecology, Mytella is likely to have a competitive advantage over Perna in estuaries like Manila Bay. (Author's abstract)